Organizational capabilities and the software project success in public sectors: process innovation as a mediator - Rozaida, Mohd Darus (2019)
Developing a software project is expensive and often a difficult process due to cost and schedule overrun. It can be argued that too much emphasis is placed by the recent approaches and models of the development of software projects on the technical skills of coding and debugging. Consequently, the importance of strategic planning and design of software is neglected. Furthermore, the higher the dynamic and turbulence of environmental changes posed on software projects, the more strategic the project procedures need to be in order to cope with these changes efficiently and effectively. This research study was conducted in order to ensure that software projects are developed on time and within the allocated cost. Based on past literature works, it was found that the resource-based view (RBV) of an organization’s competitive advantage is one of the main strategic management theories applicable to explain its success. Therefore, the organizational capabilities framework by Grantt were proposed to be adapted into the software projects in Malaysia’s public sectors. Moreover, innovation is an approach of sustaining the project’s success within a dynamic and changing environment. It is the main strategic tool for a process competitive advantage in this kind of environment. In this study, a quantitative research design was adopted where a positivist paradigm was followed. Through Smart PLS 2.0, bootstrapping was used as the nonparametric resampling procedure in order to test the mediating effect on software project success process with the respondents consisting of 228 of Malaysian IT Managers in the public sectors. As a result, it was shown that in order to achieve success, competitive advantages are essential for an organization. In addition, the significance of organizational capabilities was the focus of this study. This factor may determine how IT managers make decisions to alter their organization’s assets or capability bases. It was also suggested in this study that it is appropriate for an organization to develop its capabilities through the emerging IT infrastructure, coordinating expertise, and the development of communication plans. It is important for organizations to implement a process innovation strategy which can develop better-quality products, reduce the duration of service delivery, improve its efficiency, produce new products, and also manage staff knowledge and information. Besides, it is important for organizations to implement process innovation practices which support the organizational capabilities while delivering the product on time and within the cost allocated for the software projects.